2014
DOI: 10.2478/aoas-2013-0063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium supplementation in pig feed on slaughter value and physicochemical and sensory characteristics of meat

Abstract: the aim of the study was to examine the assimilability of organic and inorganic selenium supplied as an additive to pig feed. The influence of both selenium forms on pig slaughter value as well as on the physicochemical and sensory characteristics of meat was also examined (experiment i). an attempt to establish the distribution of selenium in the body of experimental fatteners was made (experiment ii). Experiment i was performed on 20 carcasses of crossbred pigs of (polish large White × polish landrace) × dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 11 publications
2
26
2
1
Order By: Relevance
“…That may explain the lower incidence of PSE meat in the animals supplemented with Na 2 SeO 3 . This is in accordance with the studies carried out by LISIAK et al, (2014). These authors also reported that WHC was lower in the group of pigs supplemented with selenium.…”
Section: Resultssupporting
confidence: 92%
“…That may explain the lower incidence of PSE meat in the animals supplemented with Na 2 SeO 3 . This is in accordance with the studies carried out by LISIAK et al, (2014). These authors also reported that WHC was lower in the group of pigs supplemented with selenium.…”
Section: Resultssupporting
confidence: 92%
“…More pronounced changes were observed in SM than in LTL muscle. Supplementing inorganic Se had a stronger effect on Se concentration in SM than LTL (Lisiak et al, 2014). Higher TBARS concentration after storage (Bobček et al, 2004) and higher concentrations of PUFAs, as well as Fe, Zn, Cu (Purchas et al, 2009) can be found in SM compared with LTL, so SM seems more susceptible to changes in dietary trace element concentrations.…”
Section: Resultsmentioning
confidence: 95%
“…The form of dietary Se supplementation for the domestic animals is object of study for several species, since different authors verified higher bioavailability of organic sources compared to the commonly used inorganic source (Bertechini et al, ; Calvo, Toldrá, Rodríguez, Lópes‐Bote, & Rey, ; Cao, Fucun, Liying, Bing, & Limin, ; Dalia, Loh, Sazili, Jahromi, & Samsudin, ; Lisiak et al, ; Silva et al, ). Due to the higher bioavailability and higher muscle retention, the organic sources provide better pig meat quality results, including reduced exudation losses, lower cooking loss (CL) and lower lipid peroxidation index, indicating a longer shelf life of these meats (Bobcek et al, ; Calvo et al, ; Kim & Mahan, ).…”
Section: Introductionmentioning
confidence: 99%